The Effect of Negative Pressure in the Abdominal Cavity With Suprasorb CNP on Abdominal Organs—An Experimental Study - Auer, Thomas; Wiederstein-Grasser, Iris; Sauseng, Siegfried; Delcev, Pavle; Preisegger, Karl H. (Frontiers in Surgery, 2021)
Since the introduction of negative pressure therapy of the abdomen, care has been taken to protect the intestine from the effects of negative pressure in order to avoid impairments of abdominal organs. As an alternative to the widespread AB-TheraR system, the different concept of Suprasorb CNPR was used to achieve a higher therapeutic effect in the abdomen. Due to numerous pores of the film, the effects of the negative pressure are brought to the surface of the intestinal organs and these effects were tested On 7 experimental animals. Particular attention was paid to the small intestine, colon, liver and pancreas. Over 8 hours continuously, 3 animals were tested with -80mmHg, 4 with -60mmHg. The results showed no macroscopic pathological changes. The histological results showed borderline changes in the small intestine and colon with -80mmHg application, minimal or none with -60mmHg. Liver and pancreas were found free of pathological changes. For use on human organs, the intra-abdominal application of -60mmHg for the Suprasorb CNP system is proposed as the standard.